2017
DOI: 10.1111/jerd.12346
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study comparing digital radiography and near‐infrared transillumination in caries detection

Abstract: The NIRTI system could serve as an adjunct diagnostic system that could be used in high-caries risk programs where patients are closely monitored with regimented follow-up appointments. NIRTI could also be beneficial with pregnant or pediatric patients, and in situations where radiography may not be available such as remote humanitarian missions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…W ostatnich latach opublikowano wiele prac na temat zabiegów przeprowadzonych z zastosowaniem DIAGNOcam-u, które miały na celu wykrywanie próchnicy zębów stałych zarówno na powierzchniach stycznych (13,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), jak i żujących (39)(40)(41). Zdecydowana większość doniesień dotyczy diagnostyki próchnicy pierwotnej, choć zamieszczono jedną, której tematem jest diagnostyka próchnicy wtórnej (38).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…W ostatnich latach opublikowano wiele prac na temat zabiegów przeprowadzonych z zastosowaniem DIAGNOcam-u, które miały na celu wykrywanie próchnicy zębów stałych zarówno na powierzchniach stycznych (13,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), jak i żujących (39)(40)(41). Zdecydowana większość doniesień dotyczy diagnostyki próchnicy pierwotnej, choć zamieszczono jedną, której tematem jest diagnostyka próchnicy wtórnej (38).…”
Section: Resultsunclassified
“…In recent years, many studies have been published on the procedures performed with the use of DIAGNOcam, which were aimed at detecting caries in permanent teeth on both the contact (13,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) and chewing surfaces (39)(40)(41). The vast majority of reports concern the diagnosis of primary caries, although there is one which discusses the diagnosis of secondary caries (38).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NIDIT can eliminate the patient ionizing radiation exposure. Therefore,this system could also be beneficial to pregnant or pediatric patients, and in situations where radiography may not be available [24,25]. It is also suggested that NIRTI images showed reliability and the enamel caries surfaces were better identified than on dental radiographs [26][27][28].…”
Section: Near-infrared Transillumination (Nirti) and Near-infrared Digital Imaging Transillumination (Nidit)mentioning
confidence: 99%